2022
DOI: 10.1016/j.celrep.2021.110217
|View full text |Cite
|
Sign up to set email alerts
|

Mannose-binding lectin and complement mediate follicular localization and enhanced immunogenicity of diverse protein nanoparticle immunogens

Abstract: Nanoparticle (NP) vaccine formulations promote immune responses through multiple mechanisms. We recently reported that mannose-binding lectin (MBL) triggers trafficking of glycosylated HIV Env-immunogen NPs to lymph node follicles. Here, we investigate effects of MBL and complement on NP forms of HIV and other viral antigens. MBL recognition of oligomannose on gp120 nanoparticles significantly increases antigen accumulation in lymph nodes and antigen-specific germinal center (GC) responses. MBL and complement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 74 publications
(91 reference statements)
1
37
1
Order By: Relevance
“…This suggests that despite its relatively large size, the poorly immunogenic HIV-1 Env may impart less antigenic competition with the nanoparticle scaffold than the other more immunogenic antigens. Alternatively, more efficient trafficking of HIV-1 Env immunogens to lymph nodes due to the high oligomannose glycan density on Env 25 , 81 , 82 may be another mechanism by which the immunogenicity of the underlying I53-50 scaffold is increased. Furthermore, the ratio of antigen-specific over anti-I53-50 titers for the HIV-1 Env groups was consistently less than 1 at all time points, while the other nanoparticle immunogen groups exhibited ratios equal to or greater than 1 ( Figures 3 E and S6 A).…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that despite its relatively large size, the poorly immunogenic HIV-1 Env may impart less antigenic competition with the nanoparticle scaffold than the other more immunogenic antigens. Alternatively, more efficient trafficking of HIV-1 Env immunogens to lymph nodes due to the high oligomannose glycan density on Env 25 , 81 , 82 may be another mechanism by which the immunogenicity of the underlying I53-50 scaffold is increased. Furthermore, the ratio of antigen-specific over anti-I53-50 titers for the HIV-1 Env groups was consistently less than 1 at all time points, while the other nanoparticle immunogen groups exhibited ratios equal to or greater than 1 ( Figures 3 E and S6 A).…”
Section: Resultsmentioning
confidence: 99%
“…Immunogens that can bind MBL2 and activate complement increase response to immunogens including influenza in mouse models. 48 , 49 In line with this, deletion of the downstream complement component C3 in mice was found to lower antibody response to both live influenza virus and influenza antigen. 50 There is also evidence that C2 deficiency may be associated with weak antibody response to pneumococcal vaccines.…”
Section: Resultsmentioning
confidence: 59%
“… , The role of complement in vaccine efficacy is unclear, although several studies have found a direct link. , Complement can be triggered both by immune lectins, such as MBL2 and ficolins, or by antibodies. Immunogens that can bind MBL2 and activate complement increase response to immunogens including influenza in mouse models. , In line with this, deletion of the downstream complement component C3 in mice was found to lower antibody response to both live influenza virus and influenza antigen . There is also evidence that C2 deficiency may be associated with weak antibody response to pneumococcal vaccines .…”
Section: Resultsmentioning
confidence: 76%
See 2 more Smart Citations